TATA KELOLA SYARIAH DAN RISIKO PERBANKAN TERHADAP KINERJA KEUANGAN (STUDI PADA INDUSTRI PERBANKAN SYARIAH YANG TERDAFTAR DI OTORITAS JASA KEUANGAN PERIODE TAHUN 2015-2019) - Vanny Billa Ardinna (Jurnal Kompetitif Bisnis, 2020)
This study aims to analyze the effect of sharia governance and banking riskon the financial performance of islamic banking. The dependent variable in this study is financial performance as measured by using a profitability ratio, while the independent variable in this study is sharia governance as measured by the proportion of independent commissioners and the numver of sharia supervisory board, then for banking risk is measured using credit risk, liquidity risk, and operational risk. The population used in this study were all islamic banks registered with the Financial Service Authority for the period 2015-2019 namely 34 banks. Based on the puposive sampling method, the sample obtained is 28 banks that meet the criteria. The analysis method used is panel data regression analysis using the software Eviews for Windows Version 11. The result of this study indicate that independent commissioners, sharia supervisory board, and liquidity risk partially dont have a significant effect on probability. While credit risk and operational risk partially have a significant effect on probability. Simultaneous independent, independent commissioners, sharia supervisory board, credit risk, liquidity risk, and operational risk have a signifikan effect on probabilty.